2001
DOI: 10.1007/s004310100760
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine in phenobarbital-nonresponders: experience with ten preterm infants

Abstract: This is the first report on the use of carbamazepine in small preterm infants. Carbamazepine may provide a useful and effective oral maintenance therapy in the management of neonatal seizures in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…Its use in this population has been reported previously only in two studies in term 20 and preterm neonates. 21 Consistent with these reports, none of the 17 patients in our cohort treated with CBZ as neonates and infants experienced any gastrointestinal, hepatic, hematologic, renal, or dermatologic side effects. We used a low dose of CBZ; however, since the dose was not subsequently adjusted for weight, it is possible that even lower doses may be effective.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Its use in this population has been reported previously only in two studies in term 20 and preterm neonates. 21 Consistent with these reports, none of the 17 patients in our cohort treated with CBZ as neonates and infants experienced any gastrointestinal, hepatic, hematologic, renal, or dermatologic side effects. We used a low dose of CBZ; however, since the dose was not subsequently adjusted for weight, it is possible that even lower doses may be effective.…”
Section: Discussionsupporting
confidence: 90%
“…Although, CBZ, a sodium‐channel blocker, has been used in adults and children for >30 years with an excellent therapeutic and side effect profile, it is seldom used in newborns. Its use in this population has been reported previously only in two studies in term and preterm neonates . Consistent with these reports, none of the 17 patients in our cohort treated with CBZ as neonates and infants experienced any gastrointestinal, hepatic, hematologic, renal, or dermatologic side effects.…”
Section: Discussionsupporting
confidence: 83%
“…Preliminary studies of antiepileptic drugs other than phenobarbital and phenytoin have shown only modest efficacy in smaller cohorts of neonates, although sufficiently powered randomized trials are needed to conclusively demonstrate whether any of these drugs are truly effective. 7,10,32,46,64 The lack of evidence-based treatment recommendations, coupled with the paucity of data regarding the underlying pathophysiology of neonatal seizures, has made their current management far from optimal.…”
Section: Neonatal Seizures Are a Common Problem With Inadequate Treatmentioning
confidence: 99%
“…CBZ levels dropped precipitously in 15 days, most likely from autoinduction, which also occurs in older children. Hoppen and coworkers (46) used CBZ in 10 preterm infants who had failed therapy with Pb. The initial dose was 7 to 10 mg/kg and was increased up to 23 mg/kg if seizures continued.…”
Section: Carbamazepine (Cbz)mentioning
confidence: 99%